2009
DOI: 10.1002/app.29634
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of 3‐benzothiazolthio‐1‐propyltriethoxylsilane and its reinforcement for styrene–butadiene rubber/silica composites

Abstract: A novel block mercaptosilane (3-benzothiazolthio-1-propyltriethoxylsilane) (Silane-M) was synthesized and characterized by Fourier transform infrared spectra, 1 H nuclear magnetic resonance, and elemental analysis. Styrenebutadiene rubber (SBR)/silica composites were prepared with Silane-M, and its effect on the properties of materials was studied. Results show that Silane-M can substantially improve the dispersion of silica and strengthen the reinforcement of silica for SBR vulcanizates like anchors of silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…There have also been some studies on this. C1 and N1 exhibited lower compression heat buildups (10–15°C) and compression permanent sets (2–3%) than those (18–48°C and 10–35%) reported by Peng et al A similar superiority was also reflected in a comparison with Kar's report . The compression permanent set of 5.8–6.2% and the compression heat buildups of 62.5–67°C and even 40.8–54.2°C and 85.7–92.3°C were higher than those in our study; this showed the advantage of cocoagulation technique.…”
Section: Resultssupporting
confidence: 61%
“…There have also been some studies on this. C1 and N1 exhibited lower compression heat buildups (10–15°C) and compression permanent sets (2–3%) than those (18–48°C and 10–35%) reported by Peng et al A similar superiority was also reflected in a comparison with Kar's report . The compression permanent set of 5.8–6.2% and the compression heat buildups of 62.5–67°C and even 40.8–54.2°C and 85.7–92.3°C were higher than those in our study; this showed the advantage of cocoagulation technique.…”
Section: Resultssupporting
confidence: 61%
“…This causes difficulties in processability and hampers a significant reinforcement effect . There have been several efforts to overcome this problem among which modification of silica surface by silane treatment is an important one . Also, in situ generation of silica into rubber matrix by sol–gel process has attracted attention in recent past in order to achieve better filler dispersion and improved composite properties.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies on nitrile rubber silica composites showed that γ‐mercptopropyltrimethoxysilane (γ‐MPS) acts for such rubber systems as an effective silane coupling agent in modifying the silica surface and in improving the ultimate properties of the composites . Surface modification of silica by organosilane can efficiently improve its compatibility with organic rubber matrix and increases the degree of dispersion owing to its different functionality at two ends . In general, surface modification of silica by organosilane is done by either pretreatment of silica before mixing with rubber or during physical mixing of silica with rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve the compatibility between silica and rubber matrix and the dispersion ability of silica particles in the rubber, it is necessary to modify the silica to enhance its reinforcing effects on the tread compound. The most commonly used surface modifiers are the reactive silane coupling agents . Bis‐(γ‐triethoxysilylpropyl)‐tetrasulfide (TESPT), bis‐[γ‐triethoxysilylpropyl]‐disulfide (TESPD), and mercaptopropyltriethoxysilane (MEPTS) are widely used for the modification of silica in preparing silica/rubber composites .…”
Section: Introductionmentioning
confidence: 99%